ANALISIS SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION MASKAPAI GARUDA INDONESIA PADA PENERBANGAN DOMESTIK RUTE JAKARTA-DENPASAR MENGGUNAKAN AIRLINE SERVICE QUALITY (AIRQUAL) MODEL - ANDRI FITRIANSYAH; KETUT VINI ELFAROSA; KADEK JEMMY WACIKO (GANEC SWARA, 2024)
This research carries the title "Analysis Service Quality to Customer Satisfaction Garuda Indonesia Airlines uses domestic flights on the Jakarta-Denpasar route Airline Service Quality (Airqual) Model" This research aims to determine and explain the influence Airline Tangible (X1), Terminal Tangible (X2), Personal Quality (X3), Empathy (X4), Airline Image (X5) against Customer Satisfaction. This research uses the Explanatory Research method with quantitative methods. The data collection method in this research uses an e-questioner, with a sample size of 112 respondents determined using the Slovin formula. The data analysis techniques used are the Quantitative Descriptive Analysis method, Classic Assumption Test, Multiple Linear Regression, F Test, and t-test. The results of this research are airline service quality the model has a significant